PELAKSANAAN PEMBELAJARAN FULL DAY SCHOOL (Studi Kasus di SMA Negeri 1 Kota Bangun) - Budi Yusuf (Fakultas Agama Islam Universitas Kutai Kartanegara, 2018)
The purpose of this study was to find out about the implementation of full day school learning that was implemented by SMA Negeri 1 Kota Bangun. The results obtained from this study are schools that implement full day school learning, SMA Negeri 1 Kota Bangun integrating all the daily activities of students in school into a series of learning curriculum, full day school implementation in SMA 1 Kota Bangun implemented to maximize implementation of learning by: 1. Addition to Learning Time, 2. Material enrichment from curriculum content, 3. Religious deepening by practicing it in daily life, 4. Extracurricular activities carried out to explore and sharpen the talents and potential of students.